IMPLEMENTASI ALAT BANTU PENYUSUNAN MODUL DIGITAL DALAM MENGHADAPI 21ST CENTURY LEARNING DI SMK NEGERI 1 CILEUNGSI - Nugraha, Dian; Faizah, Safira; Zaenudin, M; Hertin, RD; Udriyah; Islam, IN (Universitas Mataram, 2024)
Education plays a crucial role in building an adaptive society in the 21st-century globalization era. The learning paradigm has shifted from a teacher-centered to a student-centered approach, emphasizing critical, creative, communicative, and collaborative skills development. Technological limitations hinder the attainment of these skills, hence it is imperative for educators to leverage technology to foster innovative and engaging learning environments. This study aims to enhance the effectiveness of education at SMK Negeri 1 Cileungsi through the implementation of digital modules, preparing students for 21st-century education. Proposed methods include: 1) Socialization of 21st-century learning approaches to educators and students; 2) Intensive training in digital module usage; and 3) Provision and training on audio-visual learning material production tools as engaging and interactive learning resources. The outcomes of this community engagement initiative encompass improved understanding of 21st-century learning concepts among educators, staff, and students. Teachers will be able to integrate digital modules into the curriculum, while students will actively engage with captivating audio-visual materials. Regular evaluations will ensure implementation effectiveness and measure academic progress and students' skills in tackling modern learning challenges. Additionally, feedback from school representatives suggests extending these activities to other departments beyond Computer Networking Engineering. In conclusion, the adoption of digital modules and audio-visual materials enhances learning enthusiasm by providing adaptive learning tailored to student needs. Recommendations for enhancing school technology infrastructure and sustainably evaluating programs aim to enrich future learning experiences.